2021
DOI: 10.3390/ijerph182211787
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Acute Exposure to Wildfire Smoke and Lung Function among Royal Canadian Mounted Police (RCMP) Officers

Abstract: The increasing incidence of extreme wildfire is becoming a concern for public health. Although long-term exposure to wildfire smoke is associated with respiratory illnesses, reports on the association between short-term occupational exposure to wildfire smoke and lung function remain scarce. In this cross-sectional study, we analyzed data from 218 Royal Canadian Mounted Police officers (mean age: 38 ± 9 years) deployed at the Fort McMurray wildfires in 2016. Individual exposure to air pollutants was calculated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Their exposure profile is different from that of WLFFs as they may inhale high volumes of WFS but for shorter durations and not as frequently. Although Moitra et al 78 showed that police officers deployed during a wildfire were exposed to high levels of air pollutants (CO, NO 2 , O 3 , and PM 2.5 ), no study to date has examined the cardiovascular risk associated with WFS inhalation in this population.…”
Section: Other First Respondersmentioning
confidence: 99%
“…Their exposure profile is different from that of WLFFs as they may inhale high volumes of WFS but for shorter durations and not as frequently. Although Moitra et al 78 showed that police officers deployed during a wildfire were exposed to high levels of air pollutants (CO, NO 2 , O 3 , and PM 2.5 ), no study to date has examined the cardiovascular risk associated with WFS inhalation in this population.…”
Section: Other First Respondersmentioning
confidence: 99%
“…The heavily exposed firefighter populations are of particular interest for studies on onset of airway disease and allergic sensitization [72]. While most of the published investigations have focused on the acute effects of wildfire smoke exposure, in a study involving 218 Royal Canadian Mounted Police officers deployed during the Fort McMurray wildfires in 2016, researchers found that a marginal association between air pollution and increased residual volume (indicating potential peripheral airway effects) was significantly higher in participants who were screened within the first 3 months of deployment (2.80; 0.91–4.70) than those screened later indicating that short-term exposure to wildfire-related air pollutants may have subtle but clinically significant adverse effects on respiratory health, particularly in the peripheral airways [73]. In a different study using the Alberta Administrative Health Database, the authors identified five community-based controls for each firefighter in a cohort of 1,234 deployed to the 2016 Fort McMurray fire and estimated PM2.5 particle exposure.…”
Section: Firefightersmentioning
confidence: 99%
“…• Pediatric patients predisposed to respiratory complications are at increased risk for adverse respiratory events under anesthesia during periods of poor air quality due to wildfire smoke W ildfire activity has increased significantly over the past three decades worldwide. [1][2][3][4] In 2020, 41 major wildfire events occurred in the United States and Canada, 5 with more than 10 million acres of land burned. 6 An expanding urban-wildland interface, 7 as well as climate change 8 with warmer temperatures, earlier snowmelts, and less rainfall, have likely impacted both the severity and the frequency of fires in the western United States.…”
Section: Editor's Perspectivementioning
confidence: 99%